EFFICACY OF CORONARY STENTING AND BASIC PHARMACOTHERAPY IN ELDERLY AND SENILE PATIENTS: THE RESULTS OF LONG-TERM PROSPECTIVE FOLLOW-UP - L. R. Mirzakhanova (Столичная издательская компания, 2016)
Aim. To compare survival rate and quality of life in geriatric patients after coronary stenting or after basic pharmacotherapy only. Material and methods. 135 patients of geriatric age with ischemic heart disease (IHD) were included into the study. Coronary stenting with the subsequent basic pharmacotherapy was carried out in 70 patients, other 65 patients received basic pharmacotherapy only. Additional examinations (echocardiography , coronaroventriculography , treadmill test) were performed during the 12 months follow-up for indications other than standard clinical and laboratory examinations. Total mortality and  myocardial infarction rate, quality of life indices, and instrumental ex- aminations data were analyzed. Results. During one year after coronary stenting the overall mortality risk reduced in 3.3% and risk of non-fatal myocardial re-infarction decreased in 2.0%. Besides significant reduction in hospitalization rate, clinical improvement in stable angina course, increase in coronary heart reserve were observed in patients after PCI in comparison with these in patients received only standard pharmacotherapy. At the end of follow-up according to echocardiography data patients undergone coronary stenting shown increase in the left ventricle ejection faction (from 47.5±6.65% to 52.2±4.27%; р<0.010). This was not observed in patients with pharmacotherapy only (from 48.3±6.40% to 49.1±5.86%). Conclusion. Coronary stenting in geriatric IHD patients is an effective method of treatment. It increases quality of life due to reduction in the hospitalization rate and improves clinical course of stable angina.